MENINGKATKAN MOTIVASI, HASIL BELAJAR PENDIDIKAN AGAMA ISLAM PEMBELAJARAN COOPERATIF MODEL ARIAS KELAS V SD - ST. MURNI (Profesi | Jurnal Ilmu Pendidikan dan Keguruan, 2014)
This research is motivated characteristics of students lack confidence in teaching , research studieson the use of models PAI ARIAS ( Islamic Education ) Competency Standards ( Tarikh 3.Menceritakan story of the Prophet ) . Based on these problems , the research objectives are : ( 1 ) determine the form of the implementation of learning PAI ( Islamic Education ) subject Competency Standards ( Tarikh 3.Menceritakan story of the Prophet ) by using a model of ARIAS to improve student learning outcomes and grade IV ( 2 ) determine the increase student learning outcomes using the model of ARIAS on subjects PAI ( Islamic Education ) subject Competency Standards ( Tarikh 3.Menceritakan story of the Prophet ) class V. The method used in this research is Classroom Action Research ( CAR), which adapted the model of Kemmis & Mc . Taggart with two cycles, each cycle performed in one action . The subjects were fifth grade second semester SDN 05 Morning Kedaung Kaliangke West Jakarta , totaling 26 people . The results of the study using the model shows that in exercising their ARIAS use ARIAS models must consider the number of students that learning is more effective and efficient .In the second cycle has increased with an average value of 87 with a completeness of 100 % of students who achieved the KKM . Based on the above results it can be concluded that the use of ARIAS models can improve student learning outcomes in subjects PAI (Islamic Education ) subject Competency Standards (Tarikh 3.Menceritakan story of the Prophet ) . Based on these results , there are some suggestions that would be submitted , among other things : ( 1 ) note the number of students that learning is more effective and efficient , ( 2 ) study group should be heterogeneous for learning more meaningful